[STIX]x1D6E5-CONVERGENCES OF WEIGHTED AVERAGED PROJECTIONS IN CAT([STIX]x1D705) SPACES. (14th June 2021) - CHOI, BYOUNG JIN
Abstract: We first introduce the weighted averaged projection sequence in CAT([STIX]x1D705) spaces and then we establish some inequalities for the weighted averaged projection sequence. Using the inequalities, we prove the asymptotic regularity and the [STIX]x1D6E5 -convergence of the weighted averaged projection sequence. Furthermore, we prove the strong convergence of the sequence under certain regularity or compactness conditions on CAT([STIX]x1D705) spaces.